Design of Cutting Head for Efficient Cutting Machine of Thin-walled Stainless Steel Pipe. (2017) - Yi, Ju; Qian, Yingping; Shang, Zhiqiang; Yan, Zhihong; Jiao, Yang
Abstract: A stainless steel pipe cutting device, which is for the diameter of about 130 - 150 mm and wall thickness of 1.2 mm stainless steel pipe, is mainly used for the auto vent pipe. The problems existing in the traditional cutting methods and the part of core cutting head are comprehensively analyzed in this paper. A kinematic scheme based on double-blade symmetrical and planetary cutting machine was proposed. This scheme solved the problems of stainless steel pipe in machining incision that were caused by uneven force, shrinkage, verticality and smoothness. The cutting technology was of great significance to improve the production efficiency, save energy consumption and enhance the competitiveness of industry in the international market. The pipe cutting machine has high cutting precision, making it economically feasible.